Why Do School District Budget Referenda Fail? - Ronald G. Ehrenberg; Randy A. Ehrenberg; Christopher L. Smith; Liang Zhang (Institute for the Study of Labor (IZA), 2004)
Our paper analyzes historical data for New York State on the percentage of school board budget proposals that are defeated each year and panel data that we collected for individual school districts in the state. We find that changes in state aid have little impact on budget vote success. Defeating a budget in one year increases the likelihood that the voters will defeat a budget in the next year. Finally, districts have a larger probability of having their budget proposals defeated when their school board members have longer terms.
Keywords: I22; H71; 330; school budget votes; Schulfinanzierung; Grundsteuer; New York